UTILIZING ARTIFICIAL INTELLIGENCE TO PREDICT CONSUMER ACTIONS AND MARKET TRENDS IN E-COMMERCE (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This paper explores how artificial intelligence (AI) is transforming e-commerce by forecasting consumer behavior and detecting market trends. Through machine learning, sentiment analysis, and predictive analytics, AI enables businesses to personalize services, optimize inventory, and enhance decision-making. The integration of AI tools allows for real-time responses to shifting customer preferences, resulting in improved customer satisfaction and increased competitiveness. Ethical considerations, such as data privacy and algorithmic bias, are also discussed.